2020
DOI: 10.1017/s0007114520003748
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in CD36 is associated with dietary intake in Korean males

Abstract: Fat is one of the six types of taste. Perceived taste intensity could affect the preference for a food and whether or not it is consumed. CD36 translocates fatty acids on the cellular membrane and is involved in the oral fat-sensing mechanism. Therefore, genetic variation rs1761667 in CD36 is known to be associated with the perception of fat taste and, hence, its dietary intake. This study examined whether CD36 rs1527479 T>C, a proxy of rs1761667, is associated with fat intake and related dietary behaviour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…However, this was not evident in the current study. One interesting Korean study suggested that the cluster of differentiation 36 fat sensory related gene was associated with cruciferous vegetable intake, but not TAS2R38 bitterness receptor [ 56 ]. The use of various condiments and higher overall sodium consumption level is common in this Korean population [ 57 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this was not evident in the current study. One interesting Korean study suggested that the cluster of differentiation 36 fat sensory related gene was associated with cruciferous vegetable intake, but not TAS2R38 bitterness receptor [ 56 ]. The use of various condiments and higher overall sodium consumption level is common in this Korean population [ 57 58 ].…”
Section: Discussionmentioning
confidence: 99%